Early Medieval Thatching Needles from the Site of Torčec - Prečno pole: a Contribution to the Knowledge of the Slavic Settlement of the Drava River Basin (Archaeologia Adriatica, 2009)
The article discusses unpublished objects of bone gathered during systematic archaeological excavations at the site of Torčec-Prečno pole I in Podravina (the Drava River basin). Similar or identical objects are usually interpreted as tools for weaving together reeds, hay, or other vegetal fibers. Three such artifacts were anatomically and zoologically recognized as the tibia bones of sheep or goats (1?, 2, 3, 6). Thatching needles belong to the class of objects that served for everyday use and are frequently present in Slavic settlements, and can also be found at early medieval cemeteries. In the medieval settlements of the broader European region, they have been discovered in fortified structures, rural settlements of the open type, as well as in longterm settlements alongside churches and cemeteries. As this type of object does not exhibit any specific typologicalchronological characteristics, and is quite widely dated at both types of sites (settlements and cemeteries), from the earliest medieval period onwards, it should be noted that three examples of thatching needles (1, 2, 3) come from one closed unit, a structure dated by 14C radiocarbon dating to the period up to or around the middle of the 7th century (14C - SJ 037 (KIA 28648): BP 1439 ± 22; cal AD 624, 627, 638; 1 sigma: cal AD 604 - 612 (12.3%), cal AD 616 - 644 (56.0%); 2 sigme: cal AD 564 - 574 (2.9%), cal AD 577 - 589 (3.8%), cal AD 597 - 657 (88.7%). The dates from the analyzed charcoal range in a framework from the first half of the 7th century to the latest, in AD 657, and it can be presumed that our examples were in use during the second half of the 7th century. If the function is considered of these objects discovered in structures by an old meander of the Drava River, it should be noted that fishing must certainly have represented a significant source of food (several fragments of fish bones were discovered), and it is possible that these thatching needles would have served for the manufacture of fishing nets or reed baskets used by the ancient inhabitants of Torčec to catch fish. The results of the recent archaeological excavations as supported by the 14C dates show that a settlement existed around the middle or in the second half of the 7th century at the site of Prečno pole I at Torčec, whose inhabitants used bone thatching needles as a tool in everyday life.
Keywords: Torčec-Prečno pole I; bone thatching needles; Slavs; 7th century